Analysis of Strain Rate Dependent Tensile Behaviour of Palm-Based Elastomeric Polyurethanes - Somarathna, H.M.C.C.; Raman, S.N.; Badri, K.H.; Mutalib, A.A. (My University, 2015)
The stress-strain behaviour of elastomeric polymers, such as polyurethane (PU), exhibit high rate dependency, stress–strain non-linearity, and high pressure dependency when compared to other construction materials. Since these polymers exhibit the potential to be applied as retrofitting and protective material for various types of structural materials, in enhancing their load-carrying capacity, ductility and structural survivability under different loading regimes, it is essential to comprehensively investigate their mechanical behaviour at varying strain rates. This study was undertaken to investigate the tensile stress-strain characteristics of elastomeric PU at varying strain rates, ranging from 0.001 s-1 to 0.1 s-1 (low to intermediate). The primary emphasis of this study was on the strain rate sensitivity of the tensile properties, including the Young’s modulus, tangent modulus, ultimate tensile stress, fracture strain, and strain energy modulus. The findings indicated that stress-strain behaviour of the PU exhibited high dependence to variations in strain rates and stress–strain non-linearity. The behaviour of PU also provided good concurrence with recent studies, which explored the strain rate dependency of other elastomeric polymers.
Keywords: Dynamic loading; Polyurethane